2019
DOI: 10.3847/1538-4357/ab2c9e
|View full text |Cite
|
Sign up to set email alerts
|

The Chromospheric Response to the Sunquake Generated by the X9.3 Flare of NOAA 12673

Abstract: Active region NOAA 12673 was extremely volatile in 2017 September, producing many solar flares, including the largest of solar cycle 24, an X9.3 flare of 06 September 2017. It has been reported that this flare produced a number of sunquakes along the flare ribbon (Sharykin & Kosovichev 2018;Zhao & Chen 2018). We have used co-temporal and co-spatial Helioseismic and Magnetic Imager (HMI) line-of-sight (LOS) and Swedish 1-m Solar Telescope observations to show evidence of the chromospheric response to these sunq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…The resulting waves could produce ripples with much greater bounce heights than the usual 3 km (Kosovichev & Zharkova 1998), approaching the chromosphere. These could be seen as ripples in Ca II spectrograms occurring in the chromosphere reported for this flare by Quinn et al (2019) in SST data as was suggested for the similar observations of ripples in Ca II emission by Hinode (Kosovichev 2011).…”
Section: Detection With the Time-distance Diagramsupporting
confidence: 84%
See 3 more Smart Citations
“…The resulting waves could produce ripples with much greater bounce heights than the usual 3 km (Kosovichev & Zharkova 1998), approaching the chromosphere. These could be seen as ripples in Ca II spectrograms occurring in the chromosphere reported for this flare by Quinn et al (2019) in SST data as was suggested for the similar observations of ripples in Ca II emission by Hinode (Kosovichev 2011).…”
Section: Detection With the Time-distance Diagramsupporting
confidence: 84%
“…Further helioseismic analyses of magneto-acoustic waves in this active region were carried by ?, who also discovered fast and slow magnetoacoustic waves that occurred prior to the major sunquakes and travelled through this active region. Similar waves were also seen in Ca II line spectral observations by the Swedish Solar Telescope (SST), as recently reported by Quinn et al (2019), who linked these Ca II waves to the largest sunquake. Keeping in mind that maximum Doppler velocities of the first bounce of these acoustic waves formed in the interior measured from the HMI dopplergrams do not exceed of ±3 km/s at the photosphere as reported in Fig.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is likely that the ripples generated by this hypothetical seismic source 5 can be interfering with the ripples from this seismic source 2 generated before in the same location. These acoustic waves can have a resonant interference once suggested for the similar seismic events seen in Ca II dopplergrams by Hinode (Kosovichev 2011), thus producing the unusual seismic waves observed in Ca II emission in the chromosphere (Quinn et al 2019).…”
Section: Observed Properties Of the Sunquakesmentioning
confidence: 59%